2016
DOI: 10.5152/npa.2015.10034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Patent Foramen Ovale in Cryptogenic Stroke

Abstract: PFO, especially in terms of the etiology of cryptogenic stroke in young patients, should not be underestimated. We want to emphasize the importance of TEE in identifying potential cardioembolic sources not only in young but also in all ischemic stroke patients with unknown etiology; we also discuss the controversial management options of PFO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
0
5
0
1
Order By: Relevance
“…Accumulated data support the notion that PFO is liable for in situ thrombus formation (13,(20)(21)(22). This hypothesis is empowered by the fact that specific features, such as long-tunneled PFO, concomitant presence of ASA or Chiari's network, increase the risk of stroke (1,(23)(24)(25). These findings do not favor the paradoxical embolism hypothesis, but the deceleration of flow, blood stagnation and thrombi formation within the PFO or ASA (20,26).…”
Section: In Situ Clot Formationmentioning
confidence: 97%
See 3 more Smart Citations
“…Accumulated data support the notion that PFO is liable for in situ thrombus formation (13,(20)(21)(22). This hypothesis is empowered by the fact that specific features, such as long-tunneled PFO, concomitant presence of ASA or Chiari's network, increase the risk of stroke (1,(23)(24)(25). These findings do not favor the paradoxical embolism hypothesis, but the deceleration of flow, blood stagnation and thrombi formation within the PFO or ASA (20,26).…”
Section: In Situ Clot Formationmentioning
confidence: 97%
“…Usually, ASA is combined with PFO (60-89%), and when it does, PFO tends to be of larger size (20,40,49). Several other abnormalities have been correlated with ASA, such as atrial septal defects and mitral valve prolapse (24,33).…”
Section: Atrial Septal Aneurysmmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 30% of ischemic strokes have no identifiable cause and are labeled as cryptogenic . A number of studies have suggested an association between patent foramen ovale (PFO), a frequent finding in the general population, and cryptogenic stroke . It has been postulated that the presence of a PFO can result in paradoxical embolism—a situation where an embolus from the venous system traverses from the right to left atrium and into the systemic circulation resulting in cerebrovascular events such as stroke .…”
Section: Introductionmentioning
confidence: 99%